Structure and stress state of ion-plasma hafnium condensates - Vus, A.S.; Malykhin, S.V.; Pugachev, A.T.; Reshetnyak, E.N.; Azhazha, R.V.; Kovtun, K.V. (Functional Materials, 2007)
The 0.05-0.5 μm trick films have been obtained from GFE-1 grade hafnium target by magnetron sputtering using argon ions. Purity of the obtained films was controlled by X-ray fluorescence spectroscopy. The structure of films was explored by X-ray diffractometry. The compression residual stresses in the α-Hf films and the value of crystal lattice periods have been determined by X-ray strain measurement.